The Economic Impact of the London 2012 Olympics on the British economy : Lessons for Tourism and Infrastructure Development in Future Host Cities - Kronová, Sára (2025)
The aim of this bachelor thesis is to evaluate the economic impact of the London 2012 Olympic Games on the British economy, with a specific focus on tourism and infrastructure development. The thesis is divided into three main parts. The first chapter provides a theoretical overview of mega-events and their potential economic effects, including the motivations for hosting the Olympics. The second part analyses macroeconomic indicators such as GDP growth, unemployment, inflation, and public and private expenditures, both nationally and in London. The final part focuses on the long-term legacy of the Games, especially in relation to the regeneration of East London, the development of transportation, and changes in tourism trends and city branding. The thesis concludes with key lessons and recommendations for future Olympic host cities.